The Essential Oils of Zingiber officinale Variants - Abd Malek, Sri Nurestri; Ibrahim, Halijah; Sok Lai, Hong; Guan Serm, Lee; Kam Seng, Chan; Ali, Nor Azah Mohd. (Malaysian Journal of Science, 2005)
The essential oils of the fresh rhizomes of Zingiber officinale and its three variants obtained by hydrodistillation were analyzed by a combination of capillary GC and GCMS. The variants investigated were Zingiber officinale Rosc. var. officinale (young common ginger), Zingiber officinale var. rubrum (jahe merah), Zingiber officinale Rosc. var. rubrum Theilade (halia bara) and Zingiber officinale Rosc. var. rubrum Theilade (halia padi). This resulted in the identification of 22, 40,19 and 17 components comprising 71.8%, 89.7%, 74.4% and 84.1% of the total oils, respectively. The components were identified by comparing their Retention Indices with those reported in the literature and their mass spectral data with those from the mass spectral database. The major components of the rhizome oils were found to be: Z. officinale Rosc. var. officinale (common ginger): zingiberene (16.70%), (E,E)-Î±-farnesene (13.10%), geranial (7.60%); Z. officinale var. rubrum (jahe merah): camphene (15.76%), geranial (12.66%) and ar-curcumene (9.71%); Z. officinale Rosc. var. rubrum Theilade (halia bora): geranial (28.43%), neral (14.20%) and geranyl acetate (8.77%); Z. officinale Rosc. var. rubrum Theilade (halia padi): geranial (28.62%), neral (15.58%), Î²-sesquiphellandrene (6.44%). The investigation showed that closely related variants of ginger have one or two similar major components. Zingiberene, a characteristic component in the ginger variants is always present in the range of 3-17%. The current report is the first systematic study on the essential oil composition of the common ginger and its three variants. The study of essential oil can assist in chemotaxonomic investigation of ginger variants.